Long‐term outcomes of elderly patients with CYP2C9 and VKORC1 variants treated with vitamin K antagonists. (25th September 2017) - Nagler, M.; Angelillo‐Scherrer, A.; Méan, M.; Limacher, A.; Abbal, C.; Righini, M.; Beer, J. H.; Osterwalder, J.; Frauchiger, B.; Aschwanden, M.; Matter, C. M.; Kucher, N.; et al.
Abstract : Essentials The long‐term effects of VKORC1 and CYP2C9 variants on clinical outcomes remains unclear. We followed 774 patients ≥65 years with venous thromboembolism for a median duration of 30 months. Patients with CYP2C9 variants are at increased risk of death and non‐major bleeding. Patients with genetic variants have a slightly lower anticoagulation quality only. Summary: Background: The long‐term effect of polymorphisms of the vitamin K‐epoxide reductase (VKORC1) and the cytochrome P450 enzyme gene (CYP2C9) on clinical outcomes remains unclear. Objectives: We examined the association between CYP2C9/VKORC1 variants and long‐term clinical outcomes in a prospective cohort study of elderly patients treated with vitamin K antagonists for venous thromboembolism (VTE). Methods: We followed 774 consecutive patients aged ≥ 65 years with acute VTE from nine Swiss hospitals for a median duration of 30 months. The median duration of initial anticoagulant treatment was 9.4 months. The primary outcome was the time to any clinical event (i.e. the composite endpoint of overall mortality, major and non‐major bleeding, and recurrent VTE. Results: Overall, 604 (78%) patients had a CYP2C9 or VKORC1 variant. Three hundred and thirty‐four patients (43.2%) had any clinical event, 119 (15.4%) died, 100 (12.9%) had major and 167 (21.6%) non‐major bleeding, and 100 had (12.9%) recurrent VTE. After adjustment, CYP2C9 (but not VKORC1) variants were associated with any clinical event (hazard ratio [HR], 1.34; 95% confidence interval [CI], 1.08–1.66), death (HR, 1.74; 95% CI, 1.19–2.52) and clinically relevant non‐major bleeding (sub‐hazard ratio [SHR], 1.39; 95% CI, 1.02–1.89), but not with major bleeding (SHR, 1.03; 95% CI, 0.69–1.55) or recurrent VTE (SHR, 0.95; 95% CI, 0.62–1.44). Patients with genetic variants had a slightly lower anticoagulation quality. Conclusions: CYP2C9 was associated with long‐term overall mortality and non‐major bleeding. Although genetic variants were associated with a slightly lower anticoagulation quality, there was no relationship between genetic variants and major bleeding or VTE recurrence.